Intimate partner violence and separation: an empirical analysis - Ribeiro, Daniel Lopes (2019)
This study aims to understand the determinant factors of womans's decision of separation focusing in post-IPV cases. In addition we are interested in measuring the direct effect of the violence on the decision of separation. To do so, we made use of an innovative micro database known as PCSVDF - mulher for 2017, to estimate two bivariate probability models. The first one consists of a recursive bivariate probit model where IPV enter as a covariate of separation and the second one is a standard bivariate probit (seemgly unrelated equations).Ours results show that 22% of the abused women had chosen to separate while only 10% of gthe non-victim women had separated. The econometrics estimates point out that the variables regarding to economic independence appears as significant factors for the separation. Finally, we reiterate thar violence has a large and positive effect and the woman's decision of dissolution.